The Application of Digital Reconstruction in the Documentation and Interpretation of Candi Kampung Baru, Kota Kuala Muda, Kedah - Shamsul Bahari Abd Hadi, Mohd; Ramli, Zuliskandar; Nu’man Mohd Nasir, Muhammad; Mori, Junko (International Journal of Engineering and Technology, 2018)
The site of Candi Kampung Baru was discovered in 2015, making it one of the most recent archaeological discoveries in the Bujang Valley. 2 phases of excavation had been carried out by archaeologists from the Institute of Malay World and Civilization (ATMA), in which a single unroofed, rectangular brick structure had been unearthed. Based on the analysis of archaeological remains, the candi has been identified as a 9th-10th century structure. Using measurements taken on-site, a digital model had been constructed to visualize the ancient structure, interpret its function and facilitate potential physical reconstruction in the future.Â